2023
DOI: 10.1039/d3cc01580g
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite hydrogels for strain sensing based on optical and electrical signals: a review

Abstract: Unlike metals, ceramics, or plastics, hydrogels are semi-solid, hydrophilic polymer networks with high water content. Embedding nanostructures or nanomaterials into hydrogels can impact special properties to the composites, such as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Crosslinking : nanocomposite hydrogels can be synthesized by crosslinking pre-formed polymers with nanoparticles. 44 The nanoparticles are mixed with the polymer solution, and crosslinking agents form a three-dimensional network. Blending approach : in this method, pre-formed nanoparticles and polymers are blended to form a nanocomposite hydrogel.…”
Section: Nanocomposite Hydrogel Formulation and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinking : nanocomposite hydrogels can be synthesized by crosslinking pre-formed polymers with nanoparticles. 44 The nanoparticles are mixed with the polymer solution, and crosslinking agents form a three-dimensional network. Blending approach : in this method, pre-formed nanoparticles and polymers are blended to form a nanocomposite hydrogel.…”
Section: Nanocomposite Hydrogel Formulation and Designmentioning
confidence: 99%
“…Blending approach : in this method, pre-formed nanoparticles and polymers are blended to form a nanocomposite hydrogel. 44 The nanoparticles and polymers can be mixed using stirring, sonication, or extrusion techniques. The radical polymerization method involves using radical initiators to polymerize monomers in the presence of nanoparticles.…”
Section: Nanocomposite Hydrogel Formulation and Designmentioning
confidence: 99%
“…PAAm is selected because it is widely used as a representative and nontoxic hydrophilic polymer to synthesize isotropic hydrogels with various applications in the pharmaceutical, 29 biomedical, 30 and soft flexible sensors. 31 It is found that the cross-linker content significantly affects the mechanical properties of PAAm gels and PDGI/PAAm gels. The cross-linker content also affects the adhesion of PAAm gels, while it has little effect on the adhesion of PDGI/PAAm gels.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the effects of the cross-linker content on the mechanical properties (e.g., tensile behaviors, viscoelasticity, and crack resistance) and adhesion performances are explored in PAAm gels and PDGI/PAAm gels. PAAm is selected because it is widely used as a representative and nontoxic hydrophilic polymer to synthesize isotropic hydrogels with various applications in the pharmaceutical, biomedical, and soft flexible sensors . It is found that the cross-linker content significantly affects the mechanical properties of PAAm gels and PDGI/PAAm gels.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of ion-conductive hydrogels have achieved heat-to-electrical energy conversion, depending on the thermodiffusion effect 30 , 31 , the thermogalvanic effect 32 , 33 , and synergistic effects 34 . Based on the abovementioned skin-like gels, significant progress has also been made in temperature 35 , pressure 36 , 37 , and strain sensing 38 , 39 . Fu et al developed a tactile sensor with temperature and pressure responsiveness using a thermoelectrochemical hydrogel elastomer, and its equivalent Seebeck coefficient reached millivolts per Kelvin 40 .…”
Section: Introductionmentioning
confidence: 99%